Sustainability of farming: Revisiting Resource Dependency Theory in analysing challenges with special reference to Bangalore Rural District. - MR, Lakshmi; Vallabhaneni, Dr. Mounica (The journal of contemporary issues in business and government, 2022)
Purpose: The purpose of this research is to understand the resource-based view of the resource consumption of farmers. In farming sector there is a resource scarcity in terms of labor, seeds, electricity, water etc. The labor scarcity can be managed by own family members, but the other resources are expensive and not easy to substitute. Hence, this study tries to understand the difficulties faced by farmers in overcoming resource scarcity. Design/methodology/approach: It is a descriptive analysis based on demographic data collected from farmers using a structured questionnaire, confirmed after a pilot study. Crombec alpha was used to test the validity and it is more than 0.725. The consistency was tested by using test-reset method and t- test is used to test the consistency of data. This statistically insignificant (p>0.05). Convenient sampling is used for data collection. Findings: The Research Dependency Theory helps farmers in classifying the controllable and uncontrollable variables affecting agriculture and crop production. The examination of Research Based View Model helps farmers in acumen on crop production and sustainable development. Research limitations/implications Only one District is examined and wider research is essential, both of a qualitative and quantitative nature. Originality/value The research provides empirical support for the Resource Dependency Theory and extends the kind of its implication for farmers in facing the challenges of sustainable farming.